2009
DOI: 10.1200/jco.2009.27.15_suppl.2000
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of bevacizumab in combination with temozolomide and regional radiation therapy for up-front treatment of patients with newly diagnosed glioblastoma multiforme

Abstract: 2000 Background: Bevacizumab (BV) is a humanized monoclonal antibody directed against the vascular endothelial growth factor (VEGF). Based on the promising activity of BV in the treatment of recurrent glioblastoma, we are conducting a phase II trial to determine whether up-front treatment of newly diagnosed GBM with BV may be more advantageous than withholding BV until recurrence. In this trial, we evaluate the safety and efficacy of BV combined with standard of care radiation (RT) and temozolomide (TMZ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…No intracerebral hemorrhage or treatment-related deaths occurred during the study. Several ongoing clinical trials have also recently reported interim data on the use of bevacizumab with radiotherapy and either temozolomide or irinotecan in patients with previously untreated glioblastoma [ 80 - 86 ]. In two of the trials with longer follow-up, the addition of bevacizumab with or without irinotecan to standard radiotherapy and temozolomide was shown to provide significant benefit in PFS relative to historic controls [ 80 , 82 ].…”
Section: Clinical Experience With Antiangiogenic Agents In Glioblastomentioning
confidence: 99%
See 2 more Smart Citations
“…No intracerebral hemorrhage or treatment-related deaths occurred during the study. Several ongoing clinical trials have also recently reported interim data on the use of bevacizumab with radiotherapy and either temozolomide or irinotecan in patients with previously untreated glioblastoma [ 80 - 86 ]. In two of the trials with longer follow-up, the addition of bevacizumab with or without irinotecan to standard radiotherapy and temozolomide was shown to provide significant benefit in PFS relative to historic controls [ 80 , 82 ].…”
Section: Clinical Experience With Antiangiogenic Agents In Glioblastomentioning
confidence: 99%
“…Several ongoing clinical trials have also recently reported interim data on the use of bevacizumab with radiotherapy and either temozolomide or irinotecan in patients with previously untreated glioblastoma [ 80 - 86 ]. In two of the trials with longer follow-up, the addition of bevacizumab with or without irinotecan to standard radiotherapy and temozolomide was shown to provide significant benefit in PFS relative to historic controls [ 80 , 82 ]. In one trial having a minimum follow-up of 18 months, the regimen incorporating bevacizumab and irinotecan was associated with a median PFS that was approximately double that seen with standard therapy in patients with newly diagnosed glioblastoma (14 vs 6.9 months, respectively) [ 82 ].…”
Section: Clinical Experience With Antiangiogenic Agents In Glioblastomentioning
confidence: 99%
See 1 more Smart Citation
“…Bevacizumab, in combination with other therapies, is also under investigation as front line therapy for GBM. A Phase II trial combining bevacizumab with standard of care radiation and temozolomide has thus far demonstrated encouraging clinical responses [ 18 ]. Moreover, Phase III randomized clinical trials are currently underway to assess the efficacy of bevacizumab with current standard of care front line therapy for GBM (NCT00884741 and NCT00943826) [ 19 ].…”
Section: Standard Treatment Of Gbmmentioning
confidence: 99%
“…Recently a phase II trial of bevacizumab (10 mg/kg every 2 weeks) in combination with TMZ (75 mg/m 2 /day) and RT in 70 patients with newly diagnosed GBM has been presented. 52 After completion of RT patients are then placed on a maintenance phase of bevacizumab (10 mg/kg every 2 weeks) and TMZ (150–200 mg/m 2 /day 5 days out of every 28) until progression or 24 months. There were grade 3–4 hematological and nonhematological toxicity ( Table 2 ).…”
Section: Different Schedules Of Tmz Administrationmentioning
confidence: 99%